Hydrogen-bonding interactions and compostability of bionanocomposite films prepared from corn starch and nano-fillers with and without added Jamaica flower extract - Gutiérrez, Tomy J. (2018)
Bionanocomposite films processed by twin screw extrusion followed by thermo molding were prepared from corn starch (Zea mays) and pH-sensitive nano-clays packaged with Jamaica flower (Hibiscus sabdariffa) extract (JFE). The hydrogen (H)-bonding interactions of the materials obtained were evaluated by ATR/FTIR spectroscopy, and their influence on the physicochemical and surface properties of the materials was analyzed. The degree of biodegradability and compostability of the films was also recorded. This latter was analyzed in terms of the ecotoxicity of the films using the variations in the growth of the primary root of lettuce (Lactuca sativa) seedlings exposed to three concentrations (1, 10 and 100 μg/mL) of the powdered films as a biomarker. The addition of the JFE-containing nano-fillers strengthened the H-bonding interactions with the thermoplastic starch (TPS) matrix, and these interactions were more efficient when there were fewer steric impediments between the JFE and the TPS. Additionally, stronger H-bonding interactions produced more hydrophilic surfaces, with greater surface energy and rougher surface morphology. All the films tested were biodegradable. Our research group had previously encountered high cytotoxicity in one of the evaluated nano-clay systems, and in this study, we confirmed that this same nano-clay system produced a non-compostable material at high concentrations (100 μg/mL), as measured by its effect on lettuce seedlings. This confirms that biodegradable materials are not necessarily compostable.